L’homicide conjugal féminin, de Marie-Josephte Corriveau (1763) à Angélique Lyn Lavallée (1990) : meurtre ou légitime défense ? - Frigon, Sylvie (Criminologie, 1996)
In this article, the author examines the socio-legal relevance of the « battered woman syndrome » (BWS) in the cases of women who kill their violent partners in Canada. The legal recognition of domestic violence in these situations, in its historical context, is examined by focusing on the Supreme Court of Canada decision in the case of Angélique Lyn Lavallée in 1990. This landmark decison is used as pivotal in this discussion in order to shed light into the reasoning behind the subsequent legal decisions. The ideas proposed in this article are part of a more general exploration of the representations of femininity and their inscription in law. In discussing female conjugal homicide, the gendered nature of law and order, the pathologization of women, the « syndromisation» phenomenon and the médicalisation of violence, the author offers some insights in thinking legal strategies but more fundamentally in the social debate to continue.